The Hands-on Guide for Junior Doctors. - Donald, Anna (John Wiley & Sons, 2011)
Are you about to start the Foundation Programme? Do you know what to expect and how to thrive? The Hands-on Guide for Junior Doctors, Fourth Edition, is the ultimate, practical guide for junior doctors and medical students. It helps you tackle the emotional, intellectual and physical demands of being a new doctor and allays common insecurities to help you make the most of your time in clinical practice. This book tells you how to prepare for the daily rigours of hospital life, and will help you meet the required standard. It provides advice on getting started in placements, and helps you devel.